PIMECROLIMUS IN THE TREATMENT OF ATOPIC ECZEMA IN CHILDREN - K.E. Efendieva; Yu.G. Levina (Педиатрическая фармакология, 2008)
In the article, the authors discuss the local treatment of atopic eczema. They give data from the series of clinical studies on the application of non steroid medication in the children — calcineurin blocker pimecrolimus. This group is specifically essential in the event of the sensitive skin areas injury, where the skin absorptive capability and side effects development probability are the highest during the long term application of the topic glucocorticosteroids. The authors present to colleagues the first results of their experience in treatment of the children with atopic eczema.Key words: atopic eczema, treatment, calcineurin blockers, pimecrolimus, children.